Apakah terapi pengendalian plak dapat menurunkan keparahan rinitis alergika pada anak? (Does oral plaque control therapy reduce severity of allergic rhinitis in children?) - Haryono Utomo; Darmawan Setijanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Allergic rhinitis is one of the most common ailments in children. In clinical practice approximately 50% of patients with symptoms of rhinitis are diagnosed with non-allergic rhinitis. Positive skin prick test or specific IgE in vitro tests that are relevant to aeroallergens are conclusive diagnostic of allergic rhinitis. However, simple diagnostic method such as